2022
DOI: 10.3390/ijerph19021005
|View full text |Cite
|
Sign up to set email alerts
|

Passability of Chironomid Larvae in Granular Activated Carbon

Abstract: We conducted an experiment to confirm the passability of chironomid larvae (Glyptotendipes tokunagai) in granular activated carbon (GAC) used in water treatment plants. After injecting larvae at different growth stages (first through fourth instars) into circular columns filled with GAC, the number of individuals and their locations within the GAC columns were recorded after 168 h. We found that more than 80% of the injected larvae in the first instar and 3.3% in the second instar passed, whereas none from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was particularly notable that the larvae breakout was in their early developmental stages, specifically instar 1 and instar 2. This finding aligns with previous studies that have shown limited effectiveness of GAC columns in removing larvae from treated water [26]. In the case of the sand filter, the effective size (ES) of the sand particles and the uniformity coefficient (UC) played a crucial role.…”
Section: Larvae Breakouts From Various Types Of Filtration Columnssupporting
confidence: 90%
See 2 more Smart Citations
“…It was particularly notable that the larvae breakout was in their early developmental stages, specifically instar 1 and instar 2. This finding aligns with previous studies that have shown limited effectiveness of GAC columns in removing larvae from treated water [26]. In the case of the sand filter, the effective size (ES) of the sand particles and the uniformity coefficient (UC) played a crucial role.…”
Section: Larvae Breakouts From Various Types Of Filtration Columnssupporting
confidence: 90%
“…As organisms typically demand more energy as they mature, fourth-stage instar larvae likely had higher energy needs compared with earlier instar larvae. Consequently, a greater occurrence of cannibalism was observed during the fourth instar stage [26,38].…”
Section: Larvae Breakouts In Relation To Sand Depth In Filtration Col...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the detection of macroinvertebrates, specifically chironomid larvae, in tap water supplied by Korean water treatment facilities in July 2020 has prompted apprehension. A nationwide investigation that ensued following the initial discovery revealed that chironomid larvae were present in seven out of the 49 sites inspected [4]. The presence of these organisms in the water supply suggests that there may be issues with the water treatment process, as larvae can easily penetrate sand filters and end up in waterworks reservoirs [5].…”
Section: Introductionmentioning
confidence: 99%